Manajemen Komunikasi PT Radio Start Srasi Swara 102, 6 FM dalam Meningkatkan Mutu Pelayanan pada Pendengarnya - Ira Wahyuni; Nina Siti Siregar; Ilma Sakinah Tamsil (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
Communication Management is new trend that combines communication management between individuals in various matters relating to communication. Radio is a tool used to transmit signals by means of modulation. The title of this research is the Communication Management of PT. Radio Start Srasi Swara 102, 6 FM in Improving the Quality of Service to Listener. The main problem in this research is how the communication management carried out by PT Radio Start Srasi Swara 102, 6 FM in improving the quality of service to its listeners. This study used a qualitative descriptive approach, with the resources informants as the primary data reference books and websites as secondary data. The data collection in this research is through observation, interviews, documentation, and library studies. Based on research conducted on PT Radio Start Srasi Swara 102, 6 FM, it is found that applied communication management includes several aspects, that is Planning, Organizing, Actuating, and Controlling, and SWOT analysis. So that the program made by Start FM able to run well. In this study, it is found that the Start FM Radio program received a positive response from its listeners. They strongly agree with the Start FM Radio program because they are very up to date and know what their listeners want. With this, communication management is very effective and precise in making event program presented to listeners, so that communication management and program management are very good starting from determining the audience, broadcasting material and its execution on target.